2022
DOI: 10.3389/fnut.2022.920413
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gut Microbiota by Essential Oils and Inorganic Nanoparticles: Impact in Nutrition and Health

Abstract: Microbiota plays a crucial role in human health and disease; therefore, the modulation of this complex and yet widely unexplored ecosystem is a biomedical priority. Numerous antibacterial alternatives have been developed in recent years, imposed by the huge problem of antibioresistance, but also by the people demand for natural therapeutical products without side effects, as dysbiosis, cyto/hepatotoxicity. Current studies are focusing mainly in the development of nanoparticles (NPs) functionalized with herbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…These extremely low F values suggest a potential use of these formulations for chronic daily oral administrations deputed to the microbiota maintenance, without producing a significant impact to the other compartments of the body. The components of EOs are indeed known as potent modulators of gut inflammation and microbiota ecology [ 34 ]. It is important to consider that brain neurochemistry is affected by gut microbiota according to the so called “gut–brain axis”; in particular, the two systems cooperate in a bidirectional way, both to regulate the absorption of nutrients in the intestine by CNS and to maintain the homeostasis of the CNS by regulating the permeability of the intestinal barrier [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…These extremely low F values suggest a potential use of these formulations for chronic daily oral administrations deputed to the microbiota maintenance, without producing a significant impact to the other compartments of the body. The components of EOs are indeed known as potent modulators of gut inflammation and microbiota ecology [ 34 ]. It is important to consider that brain neurochemistry is affected by gut microbiota according to the so called “gut–brain axis”; in particular, the two systems cooperate in a bidirectional way, both to regulate the absorption of nutrients in the intestine by CNS and to maintain the homeostasis of the CNS by regulating the permeability of the intestinal barrier [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, rigorous human clinical trials are required to validate efficacy as a natural food preservative and to determine optimal dosage (71)(72)(73). The effect on the gut microbiome is promising, but it is not yet clear what specific changes in bacterial composition drive the observed health outcomes (68,74).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the essential oil emulsions in mice supplemented with Lcarnitine showed prebiotic effects on beneficial commensal bacteria, mainly the Lactobacillus genus [199]. Furthermore, a review carried out on the modulation of gut microbiota by essential oils and inorganic nanoparticles showed that essential oils are widely studied for their gastrointestinal interference, being potent modulators for gut inflammation, metabolic reactions and microbiota diversity [200].…”
Section: Dysbiosismentioning
confidence: 99%